Wahdatul ‘Ulum Perspective Systemic Thinking: Study Integration of Science in Islamic Education - Zulkipli Nasution; Selamat Pasaribu; Surianto Surianto; Ahmad Ridwan; Hasan Bakti Nasution (STAI Hubbulwathan Duri, 2023)
Systemic thinking ability is a basic potential for humans in life. This study aims to analyze the study of systemic thinking from Wahdatul 'Ulûm's perspective as a study of the integration of knowledge in Islamic education. The approach to this research is a qualitative type, with a literature study method. Sources of data and study analysis materials used scientific literature obtained from credible websites, including Google Scholar, SINTA, Science Direct, and DOAJ. The results of this study indicate that (1) the ability to think thinking is a form of optimization of the potential possessed by humans and nature as